2017
DOI: 10.1063/1.4979546
|View full text |Cite
|
Sign up to set email alerts
|

Control of lateral ferromagnetic domains in Cr2O3/Pt/Co thin film system with positive exchange bias

Abstract: We investigated the perpendicular exchange bias (PEB) switching from negativeto positive-exchange bias state for Cr2O3/Pt/Co exchange coupling thin film system exhibiting positive exchange bias phenomena. By changing Pt spacer layer thickness or measurements temperature, we demonstrated the control of two kind of intermediate state of the switching; the double hysteresis loop indicating local, non-averaged PEB, and single hysteresis loop indicating averaged PEB. We proposed the way to control the lateral ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…On the other hand when we apply a large negative E fc (antiparallel H fc and E fc ), the F − (↓↑↓↑) domain state of Cr 2 O 3 is stabilized, and a negative PEB is obtained. As we have reported earlier, 17) the magnetization curve shape of the intermediate state of PEB switching was changed by changing the PEB magnitude (Pt spacer layer thickness). Even though the loop shape is changed, we can estimate the antiferromagnetic (AFM) domain volume-fraction ratio 〈F 〉 of each sample from its magnetization curves, on the basis of the discussions in Ref.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…On the other hand when we apply a large negative E fc (antiparallel H fc and E fc ), the F − (↓↑↓↑) domain state of Cr 2 O 3 is stabilized, and a negative PEB is obtained. As we have reported earlier, 17) the magnetization curve shape of the intermediate state of PEB switching was changed by changing the PEB magnitude (Pt spacer layer thickness). Even though the loop shape is changed, we can estimate the antiferromagnetic (AFM) domain volume-fraction ratio 〈F 〉 of each sample from its magnetization curves, on the basis of the discussions in Ref.…”
supporting
confidence: 55%
“…[11][12][13][14][15] The origin of finite magnetization is still under debate; it has been attributed to piezomagnetism, boundary magnetization, etc. We have observed positive exchange-bias phenomena in Cr 2 O 3 =Pt=Co thin film systems, 16,17) which are related to the finite magnetization in Cr 2 O 3 films. Recently, we have proposed a method to achieve low-energy electric switching in Cr 2 O 3 =spacer=Co exchangecoupled systems by utilizing a finite magnetization in Cr 2 O 3 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In other systems, it was reported that the H EB altered with the change in the cooling field; it was associated with the difference in the crystalline orientations of the AFM, 16 or the coupling between the interfacial spins of the AFM layer with the external cooling field. 17,18 In our research, the independence of the E th -1/H relationship from the cooling conditions implies the stability of the interfacial spin structure under the studied conditions.…”
Section: Resultsmentioning
confidence: 60%
“…Recently, research studies motivated by device applications have also become active. For example, some studies related to the local writing of exchange bias have been exploited 65,71) for storage application; 32) further applications of this field, including the use of the spin Seebeck effect, 112) spin transport, 113) and graphene transistors, [114][115][116][117] were also reported. Further progress is expected for electrically controllable AFM Cr 2 O 3 thin films.…”
Section: Isothermal Manipulationmentioning
confidence: 99%